PolicyMap: Mapping Social Determinants of Health. Issue 3 (3rd July 2017) - Fu, Yunting; Whitfield, Sharon; Nix, Tyler
ABSTRACT: PolicyMap is a mapping resource from The Reinvestment Fund that offers access to a range of demographic and health-related data, including chronic disease incidence, health care provider locations, food access, mass transit, and other social determinates of health. This column features a sample search and describes the types of outputs available with PolicyMap.